Respostas
respondido por:
5
x² - 12x + 36 = 0
Delta = b² - 4ac
Delta = 144 - 4(1)(36)
Delta = 144 - 144
Delta = 0
X = (-b +- raiz delta) / 2a
X = (12 +- 0) / 2
x' = (12 + 0) / 2 = 12/2 = 6
x" = (12 - 0) / 2 = 12/2 = 6
Delta = b² - 4ac
Delta = 144 - 4(1)(36)
Delta = 144 - 144
Delta = 0
X = (-b +- raiz delta) / 2a
X = (12 +- 0) / 2
x' = (12 + 0) / 2 = 12/2 = 6
x" = (12 - 0) / 2 = 12/2 = 6
respondido por:
7
x² - 12x + 36 = 0
Δ = b² - 4*a*c
Δ = 144 - 4*1*36
Δ = 144 - 144
Δ = 0
como Δ = 0
só tera uma raiz entao
x' = x"
x = 12/2 = 6
Δ = b² - 4*a*c
Δ = 144 - 4*1*36
Δ = 144 - 144
Δ = 0
como Δ = 0
só tera uma raiz entao
x' = x"
x = 12/2 = 6
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás